PENGARUH KOMPOSISI PEREKAT TERHADAP EMISI FORMALDEHIDA DAN KETEGUHAN REKAT KAYU LAPIS - paribotro sutigno; suwardi sumadiwangsa (Jurnal Penelitian Hasil Hutan, 1985)
One of  the drawbacks using plywood bonded with urea formaldehvde ( UF) is formaldehyde emission, especially in a room with limited ventilation such as mobile homes. Some countries have imposed restriction on the  limit of formaldehyde emission for certain uses.This work deals with the effect of  hardener and extender types on formaldehyde emission and on bonding strength of  the UF bonded plywood.The effect of  hardener mixed with catching agent on formaldehyde emission is positive,  i.e.   lower the formaldehyde emission at the same time lower the bonding strength.   The effect of extender types were not significant.  The interaction between hardener types and extender types were highly significant. This effect, however,  was not consistent since its effect on the bonding strength was highly significant in one type of hardener only.